Aroma Terapi Peppermint dapat Menurunkan Kejadian Nausea pada Pasien Post Operasi Sectio Caesarea: Peppermint Aromatherapy Can Reduce the Incidence of Nausea in Post-Caesarean Section Patients - Teddy Setiawan; Susaldi; Elvie Tresya (Journal of Nursing Education and Practice, 2022)
Introduction: Spinal anesthesia is the main choice for cesarean section. However, spinal anesthesia can affect the occurrence of hypotension, bradycardia, apnea, inadequate breathing, and nausea/nausea, and vomiting. Aromatherapy with peppermint is one of the complementary therapies that can be an option to reduce the effects of nausea in Sectio Caesarea patients. Objectives: The objective of this study was to determine the effectiveness of peppermint therapy on the incidence of nausea in post-Sectio Caesarea patients. Method: The design used is a Quasi Experiment Design with a Non-Equivalent Control Group or Non-Randomized Group Pretest Posttest. The number of samples in this study was 30 respondents who were postoperative sectio caesarian patients in the recovery room of the Karya Bhakti Partiwi Hospital. The instrument of this study used an observation sheet. Statistical test using Wilcoxon Signed Ranks Test and Mann Whitney U Test. Results: The results of statistical tests with the Wilcoxon Signed Ranks Test in the intervention group obtained a p-value = 0.000 or <0.05. While in the intervention group the value of the control group = 0.025 or < 0.05. Conclusion: It can be concluded that there is a decrease in the incidence of nausea after giving peppermint aroma therapy.